William Blake e William Butler Yeats - Arianna, Antonielli (Biblioteca di Studi di Filologia Moderna, 2009)
Da Blake a Yeats. Sistemi simbolici e costruzioni poetiche is an investigation into the - from many aspects decisive - influence that the symbolic system and visionary poetry of the great English romantic William Blake had on the imagination of William Butler Yeats from his earliest youth. This authentic poetic and visionary apprenticeship in the work of Blake, which culminated in 1893 in the edition in three volumes accompanied by an exhaustive introduction and commentary: The Works of William Blake Poetic, Symbolic, and Critical, was decisive for the formation of the symbolic system that was to nourish all Yeats' poetry. Adopting an approach to the reading that unfurls from an initial analysis of Blake's poetic corpus, and hence from the mythical-symbolic pantheon that surfaces from this, the book then traces Yeats' initial particular hodos chameliontos, profoundly marked by magical and esoteric experiences, subsequently entering into the meanders of the aesthetic, philosophical and poetic interrelations between the symbolic system of William Blake and that of W. B. Yeats. Da Blake a Yeats illuminates how The Works of William Blake represents the first genuine formalisation of Blakeian and esoteric teachings within Yeats' system, while also representing, for Yeats himself, a keystone in his vision of Blake and an inexhaustible spring for the evolution of his symbolic system and his imagination.